2024
DOI: 10.3390/toxics12010066
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Release of Cadmium Ions in the Lichen Evernia prunastri (L.) Ach. and Wood-Derived Biochar: Implication for the Use of Biochar for Environmental Biomonitoring

Andrea Vannini,
Luca Pagano,
Marco Bartoli
et al.

Abstract: Biochar (BC) boasts diverse environmental applications. However, its potential for environmental biomonitoring has, surprisingly, remained largely unexplored. This study presents a preliminary analysis of BC’s potential as a biomonitor for the environmental availability of ionic Cd, utilizing the lichen Evernia prunastri L. (Ach.) as a reference organism. For this purpose, the lichen E. prunastri and two types of wood-derived biochar, biochar 1 (BC1) and biochar 2 (BC2), obtained from two anonymous producers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Studies showed that low-temperature pyrolysis biochar was more likely to age and decompose in the soil [13]. The Se in Acid-W300-Se will be continuously released with biochar aging to increase a crop's Se content [42,44,45].…”
Section: Red Soil Extractmentioning
confidence: 99%
“…Studies showed that low-temperature pyrolysis biochar was more likely to age and decompose in the soil [13]. The Se in Acid-W300-Se will be continuously released with biochar aging to increase a crop's Se content [42,44,45].…”
Section: Red Soil Extractmentioning
confidence: 99%